2017
DOI: 10.1021/acsomega.7b01526
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Oxidative α-Hydroxylation/β-Acetalization Reaction of β-Ketoamides and Its Applications

Abstract: A tandem oxidative α-hydroxylation/β-acetalization reaction of β-ketoamides was developed in the presence of PIDA and NaOH. This reaction proceeded at 25 °C in the absence of a metal catalyst to provide 2-hydroxy-3,3-dimethoxy- N -substituted butanamides in good to excellent yields from readily available starting materials. The application of this chemistry to the construction of α-hydroxy-β-ketoamides and quinolinones was also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Recently, we developed two facile, reliable, mild, and efficient β‐ketoamide functionalization reactions for the synthesis of 2‐hydroxy‐3,3‐dimethoxy‐ N ‐substituted butanamides and vicinal tricarbonyl amides in the presence of a hypervalent iodine reagent via an oxidative C−O bond forming reaction . While further exploring the synthetic potential of β‐ketoamides in the presence of an organoiodine reagent, a catalytic amount of CuCl catalyst (10 mol %) was added to the reaction of 1 a in MeOH solvent. The resulting product, 2 a , was isolated and further characterized by NMR analysis.…”
Section: Figurementioning
confidence: 99%
“…Recently, we developed two facile, reliable, mild, and efficient β‐ketoamide functionalization reactions for the synthesis of 2‐hydroxy‐3,3‐dimethoxy‐ N ‐substituted butanamides and vicinal tricarbonyl amides in the presence of a hypervalent iodine reagent via an oxidative C−O bond forming reaction . While further exploring the synthetic potential of β‐ketoamides in the presence of an organoiodine reagent, a catalytic amount of CuCl catalyst (10 mol %) was added to the reaction of 1 a in MeOH solvent. The resulting product, 2 a , was isolated and further characterized by NMR analysis.…”
Section: Figurementioning
confidence: 99%
“…This reaction provides the most straightforward access to the α-hydroxy-β-dicarbonyl, an intriguing moiety commonly found in various biologically active natural products, agrochemicals, and pharmaceuticals [25][26][27]. Notably, a number of chemical protocols are available to accomplish this oxidation to yield product 2 [28][29][30][31][32][33]. For instance, Lu et al reported a Brønsted acid catalytic method with nitrosobenzene as the oxygen source [28], and Meng and co-workers documented a Zr(IV)/organic peroxide system [30].…”
Section: Introductionmentioning
confidence: 99%